(untitled) (Architecture Image Studies, 2026)
Background. The representation of racial oppression in film is constructed not only through narrative and dialogue, but also through the construction of space and architectural imagery. Space and buildings serve as visual media that reflect power relations, segregation, and social control within specific historical contexts. Aim. This study aims to analyze the role of architectural imagery in shaping ethnic narratives that represent physical, psychological, and verbal oppression in the films 12 Years a Slave and Hidden Figures. Methods. The study uses an ethnonarrative approach by analyzing space, buildings, and visual design as narrative elements. The analysis focuses on the relationship between spatial representation and the characters’ ethnic experiences within the film’s narrative structure. Results. The results indicate that 12 Years a Slave represents the spaces of slavery—plantations, barracks, and work areas—as closed and repressive architectures of domination, directly controlling the bodies and movements of slaves and legitimizing physical and psychological violence. In contrast, Hidden Figures depicts modern institutional spaces—offices, laboratories, and public facilities—as seemingly neutral, yet symbolically embodying practices of segregation and restricted access. Conclusions. This research confirms that architectural imagery plays an active role in constructing ethnic narratives and represents a historical shift in forms of oppression from overt violence to more subtle, systemic control.